Problems and Settlement of Transfer of Accounts Receivable Through Cessie Against Bad Credit - Anggraeny, Isdian; Hidayah, Nur Putri; Indri Hapsari, Dwi Ratna; Azizah, Diva Ainunn (KnE Social Sciences, 2024)
Cessie is a method of solving loan problems for default debtors. Through Cessie there is a transfer of receivables originating from debtors to new creditors. However, the legal facts that occurred, in the process of implementing the Cessie also experienced legal problems. Therefore, this writing with an empirical juridical approach will identify other legal problems that arise in Cessie and analyze the legal settlement of Cessie problems that occur in state-owned banks. Based on the studies that have been done, it is concluded that the legal problems that occur are creditors who secretly transfer their receivables through a Cessie to other new creditors, even though this is normatively justified in Article 613 of the Civil Code. However, in fact, the debtor’s denial and non-approval often occur, causing new problems with new creditors. The settlement efforts made by BUMN Banks in this problem are by giving a warning letter to the debtor. Keywords: Cessie, bad credit, accounts receivable